2015
DOI: 10.1002/dac.2928
|View full text |Cite
|
Sign up to set email alerts
|

A load‐balancing and coding‐aware multicast protocol for mobile ad hoc networks

Abstract: Summary In this paper, we propose a Load‐Balancing and Coding‐Aware Multicast (LCM) protocol for mobile ad hoc networks. In LCM protocol, a new route metric named Expected Transmission Time with Coding and Load Balancing (ETTCL) is presented at first, aiming at effectively selecting the path not only that has the possible coding opportunity but also where overflow due to network overload can be prevented. Then, we describe the route discovery phase by constructing the node‐disjoint multicast tree on the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Moreover, in other analogous networks such as mobile cloud computing, 115 peer-to-peer networks, 116 machine-tomachine networks, 117 and mobile ad hoc networks 118 can use an SDN-based solution to cater load balancing. In the future, it is another research direction.…”
Section: Open Issuementioning
confidence: 99%
“…Moreover, in other analogous networks such as mobile cloud computing, 115 peer-to-peer networks, 116 machine-tomachine networks, 117 and mobile ad hoc networks 118 can use an SDN-based solution to cater load balancing. In the future, it is another research direction.…”
Section: Open Issuementioning
confidence: 99%
“…Rong Geng et al in [11] observed that most of the multicast routing protocols have not exhibited the load balancing property, which leads to network congestion. Hence, performance of the multicast routing protocol decreases.…”
Section: Related Workmentioning
confidence: 99%
“…It has provided a multipath routing protocol where a source node discovers multiple paths for sending the packets to the destination node, whereas the existing algorithms [15][16][17][22][23][24][25][26][27][28][29] find only a single path from source to destination node. It distributes the load among multiple paths periodically, whereas most of the existing works such as [5][6][7][9][10][11] use the alternate paths only when the existing path breaks. In order to distribute the load on the multiple paths, it uses the minimum queue length along a path and round-trip time for route discovery procedure as key parameters, whereas FMLB routing protocol uses the Fibonacci numbers and hop count for distributing the load on multiple paths [30,31].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations